2000
DOI: 10.1002/1096-9101(2000)27:3<255::aid-lsm7>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of low-level laser irradiation at 660 nm on peripheral blood lymphocytes

Abstract: The present study supports the hypothesis that one mechanism for the photobiostimulation effect after irradiation at 660 nm is the reaction of light with hemoglobin, resulting in oxygen radical production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
2
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 24 publications
1
73
2
8
Order By: Relevance
“…The beneficial effects of red light on the skin have been suggested by many studies [35][36][37][38][39][40][41][42][43][44][45]. It has been demonstrated by an in vitro study that red light influenced cytokine release from macrophages, which consequently stimulated fibroblast proliferation [35].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The beneficial effects of red light on the skin have been suggested by many studies [35][36][37][38][39][40][41][42][43][44][45]. It has been demonstrated by an in vitro study that red light influenced cytokine release from macrophages, which consequently stimulated fibroblast proliferation [35].…”
Section: Discussionmentioning
confidence: 88%
“…Karu [38,39] suggested that absorption of red and near-infrared light by photoacceptor molecules within the respiratory chains can cause alteration in the redox status of the cells and activate the nucleic acid synthesis to accelerate cell proliferation. Additionally, Lanzafame and his colleagues showed that low-level laser irradiation at a wavelength within visible red waveband can produce various beneficial effects such as stimulation of cell proliferation, release of growth factors, collagen deposition, and neovascularization [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…As a treatment principle, it is based on photobiomodulation effects which influence the components in the respiratory chain as primary photon acceptors. [1][2][3] Among other things, LLLT may increase cell proliferation [4][5][6] and have a positive impact on energy metabolism 1) , as well as improving microcirculation 7) and releasing growth factors. 8) Thanks to these postulated effects, LLLT is of particular interest in wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, IVLBI has been shown to have a positive influence on rheological properties of the blood; for example, it leads to a decrease in blood viscosity [12], which is of great interest to surgery and cardiology. In addition, helium-neon (He-Ne) laser irradiation induced an increase in phagocytic activity and structural modulation of macrophages [13,14] as well as proliferation of lymphocytes [15,16].…”
Section: Introductionmentioning
confidence: 99%